تمثلات العنف في الشعر الأندلسي: اليهود والنصارى أنموذجا - الفنداوي، علي غانم فلحي; نعيمه، علي مطشر (المنتدي الوطني لأبحاث الفكر والثقافة, 2019)
العنف ظاهرة قديمة قدم الإنسان تضرب بجذورها في التاريخ، وترتبط بوجود الصراع بين الحق والباطل، وبين الخير والشر، وحاول البحث الوقوف عند هذه الظاهرة في الشعر الأندلسي، وبدورنا نعمل على محاورتها، واستنطاقها، وكشف مدلولاتها، في كثير من النصوص الشعرية، التي تضمنت هذه الظاهرة، والفئات الاجتماعية التي طالها العنف؛ لأسباب سياسية، ودينية من طبقات المجتمع الأندلسي.
Violence is an ancient human phenomenon rooted in history and linked to the existence of the conflict between truth and falsehood, between good and evil, and the research has tried to stand up to this phenomenon in Andalusian poetry and in our role we are working on its axes and questioning and revealing its meanings in many poetic texts, Phenomenon, and social groups that have been plagued by violence for political and ethnic reasons from the layers of Andalusia society.
Keywords: الشعر العربى -- الشعر الأندلسى -- العنف الفكرى -- اليهود -- النصارى -- النقد الأدبى